Játék a tér - Pelsőczy, Petra (Hungary, 2011)
A documentary about the mysteries of the so-called 'lottery-houses' in Budapest, Hungary. The people in the documentary have one thing in common: they all won a flat during the days of the fashionable lottery game - between 1958 and 1968. The film explores the unique places where only winners have been living and tries to answer to several questions.
Verzio Film Festival Submission
Keywords: Documentary films